(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the knowledge and related factors regarding postoperative pain management among nurses at Le Van Thinh Hospital in 2025. Methods: A descriptive cross-sectional study was conducted on 81 nurses working in surgical departments at Le Van Thinh Hospital. The “Nurses’ Knowledge and Attitudes Survey Regarding Pain” (NKASRP, 2012 version), which has been widely used in studies in Vietnam, was employed to evaluate nurses’ knowledge of pain management in this study. Results: The study found that 39.5% of nurses achieved the required level of knowledge regarding postoperative pain management. The proportion of correct answers across items ranged from 23.5% to 88.9%, with the highest scores in clinical management and medication selection, and the lowest in pharmacokinetics-related items such as the duration of action of morphine and paracetamol. Factors associated with adequate knowledge included educational level and personal pain experience. Nurses with a bachelor’s degree were 4.81 times more likely to achieve adequate knowledge compared to those with a diploma or associate degree; those who had experienced severe pain were 3.636 times more likely to achieve adequate knowledge compared to those who could not recall their pain experience. No statistically significant associations were found between knowledge level and gender, age, work experience, or prior training. Conclusion: Nurses’ knowledge regarding postoperative pain management remains limited, with only 39.5% meeting the required level. Higher educational attainment and personal pain experience were associated with better knowledge. Therefore, continuous training and advanced education in pain management are needed to enhance nurses’ clinical competence and improve the quality of postoperative patient care.